Analisis Kesulitan Guru dalam Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) di SD Negeri 2 Gerimak Indah - Firman Jundi; Asrin; Nurul Kemala Dewi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Pancasila Student Profile Strengthening Project (P5) is one of the programs in the Merdeka Curriculum aimed at shaping students’ character in accordance with the values of Pancasila through project-based learning. However, in its implementation, teachers still face various challenges, particularly in the planning, implementation, and evaluation of P5 activities. This study aims to analyze the difficulties teachers face in implementing the Pancasila Student Profile Strengthening Project (P5) at Gerimak Indah Public Elementary School No. 2 and to identify the supporting and inhibiting factors that influence its implementation. This study employs a qualitative approach using a descriptive research design. The research subjects include the principal, teachers, and students selected through purposive sampling. Data were collected through observation, structured interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that teachers face difficulties in developing project modules aligned with the P5 themes, managing the time allocation for implementation, conducting character-based assessments, and comprehensively understanding the concepts and stages of P5. Factors supporting the implementation of P5 include support from the school principal, collaboration among teachers, and the availability of supportive school facilities and environment. Meanwhile, inhibiting factors include budget constraints, a lack of training, and a shortage of references and external partners. It is concluded that enhancing teacher competence through ongoing training and adequate resource support is essential to optimize the implementation of P5 in elementary schools.